2018
DOI: 10.1186/s13059-018-1574-2
|View full text |Cite
|
Sign up to set email alerts
|

LncRNAs in polyploid cotton interspecific hybrids are derived from transposon neofunctionalization

Abstract: BackgroundInterspecific hybridization and whole genome duplication are driving forces of genomic and organism diversification. But the effect of interspecific hybridization and whole genome duplication on the non-coding portion of the genome in particular remains largely unknown. In this study, we examine the profile of long non-coding RNAs (lncRNAs), comparing them with that of coding genes in allotetraploid cotton (Gossypium hirsutum), its putative diploid ancestors (G. arboreum; G. raimondii), and an F1 hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 88 publications
12
63
1
Order By: Relevance
“…This is consistent with the apparent conservation of TE proportions between Cucurbita species, suggesting that TEs did not play an important role in lincRNA family evolution within Cucurbita after the whole-genome duplication, unlike in other taxa such as vertebrate species, where TEs play an important role in lincRNA birth (Kapusta et al, 2013). Our results also differ from those obtained in cotton, where a larger proportion of lincRNAs were homologous to TEs than to protein-coding loci (Zhao et al, 2018). This suggests that the evolutionary dynamics of lincRNAs can change drastically between different plant taxa.…”
Section: Molecular Plantsupporting
confidence: 88%
See 1 more Smart Citation
“…This is consistent with the apparent conservation of TE proportions between Cucurbita species, suggesting that TEs did not play an important role in lincRNA family evolution within Cucurbita after the whole-genome duplication, unlike in other taxa such as vertebrate species, where TEs play an important role in lincRNA birth (Kapusta et al, 2013). Our results also differ from those obtained in cotton, where a larger proportion of lincRNAs were homologous to TEs than to protein-coding loci (Zhao et al, 2018). This suggests that the evolutionary dynamics of lincRNAs can change drastically between different plant taxa.…”
Section: Molecular Plantsupporting
confidence: 88%
“…Studies regarding the evolutionary dynamics of lncRNAs are limited despite their evident importance in plant biology, due to a traditional focus on protein-coding genes in genome-wide studies (Ulitsky, 2016;Nelson et al, 2017). Furthermore, evolutionary analyses of these genes have been limited due to a lack of conservation at both the sequence level and the secondary structure level (Ulitsky, 2016), and research on their origin and evolution is still scarce (see Necsulea et al, 2014;Nelson et al, 2016;Zhao et al, 2018). Several hypotheses have been proposed to explain the emergence of new lncRNAs, such as the neofunctionalization of duplicated protein-coding genes, co-option of transposable elements in the genome, duplication followed by neofunctionalization from other lncRNAs, and de novo emergence (Kapusta et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon may be due to the regulation at the transcriptional or post‐transcriptional level. It has been reported that the activated expression of lncRNAs in interspecific hybrids was correlated with the demethylation of transposable elements (TEs) (Zhao et al ., ). We also found that citrus TE exhibited biased distribution toward lincRNA loci rather than protein‐coding genes and lincRNA loci contained significantly more TE segments at the exon and intron sequences compared with protein‐coding gene loci (Figure S12).…”
Section: Discussionmentioning
confidence: 97%
“…Although lincRNAs have been widely identified in plants, lincRNA conservation among different species remains largely unknown. Interspecies conservation of plant lincRNAs has been evaluated between distantly related rice and maize (Wang et al ., ), between two modern tomato species and one wild tomato species (Wang et al ., ), among four closely related cotton genomes (Wang et al ., ), and among tetraploid, diploid and F1 hybrid cotton (Zhao et al ., ). This study covered nine closely related citrus species and expanded the research scope to include primitive and modern citrus.…”
Section: Discussionmentioning
confidence: 99%
“…However, hybrids often show a large spectrum of phenotypes, including extreme values that are unexpected given the parental traits (Rieseberg et al 1999;Landry et al 2007;Maheshwari & Barbash 2011;Bar-Zvi et al 2017). Indeed, previous studies have demonstrated the importance of large-scale regulatory rewiring in hybrids that impacts many processes and molecular phenotypes such as nucleosome positioning, translation efficiency, protein abundance, methylation, transcription of non-coding RNA, and the replication program (Landry et al 2007;Tirosh et al 2010;Tirosh & Barkai 2011;McManus et al 2014;Zhu et al 2017;Bar-Zvi et al 2017;Bamberger et al 2018;Zhao et al 2018).…”
Section: Introductionmentioning
confidence: 99%